A Bidding Assessment Framework using CRITIC and MABAC Methods - Radhi, Ahmed Reyadh; Nassar, Yasser Sahib; Alhilli, Hassan Kamal (Engineering, Technology & Applied Science Research, 2025)
The bidding process is instrumental for contractors and ensures work continuity and company survival. Even if the decision made to proceed with work contracting is confirmed, bidding preparation is one of the main factors effecting profit percentage. A bidding system must be built with high flexibility in order to be widely applicable and able to deal with data diversity. This paper introduces a new application of MABAC and CRITIC methods to cope with this need. The assessment framework consists of multi-attributive border approximation area comparison and criteria importance through inter-criteria correlation. A comparison made between the results gained from the proposed framework and the conventional process reveals a major difference in preference results.